Balancing Politics and the Dispersal of Business Revenues among First Nations in Saskatchewan, Canada - Natcher, David C.; Allen, Tom; Schmid, Trina (Journal of Aboriginal Economic Development, 2014)
In this paper we present the results of interviews conducted with 14 First Nations in Saskatchewan on the ways in which they balance the need for economic development while meeting the social welfare needs of community members. Specific themes include (i) the separation between business and politics; (ii) the existence and role of boards of directors; (iii) strategic versus reactive decision-making; and (iv) the tension between revenue reinvestment and disbursement. Among the First Nations interviewed, three have put into place formal structures to separate business from politics, and have prioritized strategic and long-term investment over revenue dispersal. The remaining 11 First Nations use economic development as a vehicle to meet the social welfare needs of community members, including the funding of social program, Elders care, family allowances, and host of other social welfare services. This paper offers insight into the challenges First Nation governments encounter as they struggle to meet the diverse needs of their citizenry.